Performance Comparison of the Differential Evolution and Particle Swarm Optimization Algorithms in Free-Space Optical Communications Systems - Basgumus, Arif; Namdar, Mustafa; Yilmaz, Gunes; Altuncu, Ahmet (UNIV SUCEAVA, FAC ELECTRICAL ENG, 2015)
In this comparative study we evaluate the performance of Differential Evolution (DE) and Particle Swarm Optimization (PSO) algorithms in free space optical communications systems. In particular we obtain the optimal transmission distances for different relay nodes in the parallel decode-and-forward relaying schemes by optimizing the relay placements. We analyze that the cost functions are suitably minimized. Then we investigate the execution time and the stability of the DE and PSO algorithms for decode-and-forward relay-assisted free space optical links. The simulation results demonstrate that the PSO algorithm outperforms DE algorithm in terms of the minimization of the cost function. Furthermore the results indicate that we get the similar performance for the execution-time and optimization results in the DE and PSO algorithms.
Keywords: communication systems; cooperative systems; distance measurement; evolutionary computation; particle swarm optimization; GENETIC ALGORITHM; Computer Science; Engineering